Magnetron Sputtering Deposition of Ag/TiO2 Nanocomposite Thin Films for Repeatable and Multicolor Photochromic Applications on Flexible Substrates. Issue 14 (11th August 2015) - Diop, Daouda Keïta; Simonot, Lionel; Destouches, Nathalie; Abadias, Grégory; Pailloux, Frédéric; Guérin, Philippe; Babonneau, David
<x xml:space="preserve">Abstract</x> It is reported on a reactive magnetron sputtering‐based deposition method to synthesize, at room temperature, photochromic nanocomposite thin films consisting of Ag nanoparticles sandwiched between nanoporous TiO2 layers. The fabrication process is compatible with large‐scale production and functional flexible substrates. It is shown that when TiO2 is deposited in the metallic mode, the formation of Ag metal nanoparticles induces localized surface plasmon resonances in the visible range and therefore the as‐deposited samples are colored. In contrast, when TiO2 is deposited in the compound mode, the trilayer samples are colorless because silver oxidizes during TiO2 deposition. It is demonstrated that the colorless samples can be colored under ultraviolet (UV) laser exposure at 244 nm due to the reduction of oxidized silver and the formation of metallic Ag nanoparticles. Moreover, irradiation at 647 nm wavelength of colored samples (as‐prepared or after UV exposure) gives rise to changes in the particle morphology that strongly modifies the film absorbance and results in a color transition from blue to orange. The choice of the irradiation wavelength allows controlling the color saturation of the sample up to the complete discoloration by using a visible laser at 488 nm. All these photochromic mechanisms are repeatable during cyclic processes.